2011
DOI: 10.1590/s0365-05962011000100007
|View full text |Cite
|
Sign up to set email alerts
|

Leishmaniose tegumentar americana: estudo clínico, epidemiológico e laboratorial realizado no Hospital Universitário de Campo Grande, Mato Grosso do Sul, Brasil

Abstract: FUNDAMENTOS: Leishmaniose Tegumentar Americana é zoonose de manifestações clínicas variadas, em expansão no Brasil, sendo o estado de Mato Grosso do Sul importante área endêmica. OBJETIVOS: Avaliar clínica, epidemiológica e laboratorialmente pacientes com Leishmaniose Tegumentar Americana , atendidos no Hospital Universitário Maria Aparecida Pedrossian, Universidade Federal de Mato Grosso do Sul, Brasil (HU/UFMS). MÉTODOS: Trata-se de um estudo observacional do tipo transversal com abordagem descritiva e analí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
16

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 17 publications
2
21
0
16
Order By: Relevance
“…Therefore, we can infer that the limitation factors that have been observed for other laboratory methods, such as contamination by secondary microorganisms 4 33 , the age of infection, cross-reaction to antigens or other reagents that are used in antigen production, the intrinsic characteristics of the parasite, and the pre-treatment of patients 22 does not seem to influence the kDNA-PCR results. In addition, the molecular method has several advantages: complex procedures are not required to collect and to maintain DNA samples for PCR reaction, in contrast to in vitro culture and DI test.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, we can infer that the limitation factors that have been observed for other laboratory methods, such as contamination by secondary microorganisms 4 33 , the age of infection, cross-reaction to antigens or other reagents that are used in antigen production, the intrinsic characteristics of the parasite, and the pre-treatment of patients 22 does not seem to influence the kDNA-PCR results. In addition, the molecular method has several advantages: complex procedures are not required to collect and to maintain DNA samples for PCR reaction, in contrast to in vitro culture and DI test.…”
Section: Discussionmentioning
confidence: 93%
“…In our study, we also observed that 25 of the 29 samples presenting negative results by MST were positive when evaluated by kDNA-PCR amplification (Table 2). We noted that 17 of these 25 kDNA-PCR positive samples came from sCL patients, and eight samples from sML patients, which could indicate a recent infection or a weak response from the immune system of the patients 12 25 29 33 . In contrast, one patient that presented positive result for MST was considered negative by kDNA-PCR.…”
Section: Discussionmentioning
confidence: 98%
“…Em uma pesquisa realizada no hospital universitário de Campo Grande, no estado de Mato Grosso do Sul, também foi encontrado resultados semelhantes a essa pesquisa, onde (72,3%) dos casos de LTA eram compostas por homens e (27,7%) por mulheres. Com base nesses resultados podemos inferir que a leishmaniose tegumentar americana é uma doença que está relacionada ao trabalho, porque acometem principalmente os homens em idade produtiva 13 .…”
Section: Os Dados Categóricos Foram Descritos Emunclassified
“…É uma doença multissistêmica onde os sinais clínicos podem ser extremamente variáveis (Leite et al, 2008;Murback et al, 2011;Brazuna et al, 2012;Sousa, 2013).…”
Section: Introductionunclassified
“…Programas para detecção da doença preconizam a realização de verificação sorológica em cães, com o intuito de conhecer as áreas endêmicas com transmissão ativa ou de possível transmissão e com a identificação de animais soropositivos (Brazuna et al, 2012). Contanto, Murback et al (2011), cita a importância de testes parasitológicos, sendo mais sensíveis e imediatos para controle da enfermidade.…”
Section: Introductionunclassified